2007
DOI: 10.1007/s11409-007-9013-x
|View full text |Cite
|
Sign up to set email alerts
|

SEEK Web tutor: fostering a critical stance while exploring the causes of volcanic eruption

Abstract: We investigated the impact of a Web tutor on college students' critical stance and learning while exploring Web pages on science. Critical stance is an aspect of self-regulated learning that emphasizes the need to evaluate the truth and relevance of information as the learner engages in systematic inquiry to answer challenging questions. The Web tutor is called SEEK, an acronym for Source, Evidence, Explanation, and Knowledge. The SEEK Tutor was designed to promote a critical stance through several facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 31 publications
1
36
0
3
Order By: Relevance
“…By using a broader assessment design space, we can provide scores that are potentially more reflective of the situations we want and encourage students to read within them. Students should be problem solvers and decision makers (NGACBP & CCSSO, 2010), critical evaluators of sources and evidence (Graesser et al, 2007;Lawless et al, 2012;Metzger, 2007), and collaborators in the co-construction of knowledge (Partnership for 1. To provide a purpose for reading: establishing a standard of coherence.…”
Section: Six Features Defining Scenario-based Assessmentmentioning
confidence: 99%
“…By using a broader assessment design space, we can provide scores that are potentially more reflective of the situations we want and encourage students to read within them. Students should be problem solvers and decision makers (NGACBP & CCSSO, 2010), critical evaluators of sources and evidence (Graesser et al, 2007;Lawless et al, 2012;Metzger, 2007), and collaborators in the co-construction of knowledge (Partnership for 1. To provide a purpose for reading: establishing a standard of coherence.…”
Section: Six Features Defining Scenario-based Assessmentmentioning
confidence: 99%
“…Focusing on the first activity, prior research showed that facing disparity serves as a trigger for further information search about a topic (e.g., Graesser et al, 2007;Johnson & Johnson, 2009). According to Gress, Fior, Hadwin, and Winne (2010), this further information search can stimulate students to recognize their own trouble spots.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The SEEK (Source, Evidence, Explanation, and Knowledge) web tutor was designed to help college students improve their critical thinking by evaluating the credibility and relevance of information as part of the scientific inquiry process (Graesser et al 2007c). SEEK did not use a full dialog system, but instead embedded spoken hints and structured note-taking to evaluate the information hit during a constrained web search (seven cached sites).…”
Section: Learning About Thinking: Metacognitionmentioning
confidence: 99%